2017
DOI: 10.1515/bot-2016-0094
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of daylength, temperature and nutrients affect thresholds for life stage transitions in the kelp Laminaria digitata (Phaeophyceae)

Abstract: Kelp beds worldwide are under pressure from ongoing climate and environmental change. Along European coastlines increases in seawater temperature and changes in nutrient conditions occur where upwelling events are disrupted and also along eutrophicated coasts. In addition, seaweed responses to change may interact with seasonal daylength cycles. We performed a factorial experiment to examine the combined effects of seawater temperatures, nutrient regimes and photoperiod (long and short days) in order to better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 57 publications
8
72
1
Order By: Relevance
“…, Martins et al. ). Microscopic observations showed that the young sporophytes only developed on the bottom of the well plates, and all were counted per triplet of the experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Martins et al. ). Microscopic observations showed that the young sporophytes only developed on the bottom of the well plates, and all were counted per triplet of the experimental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…), and nutrient availability (Harries , Martins et al. ). Light intensity has been described as a generic abiotic factor controlling gametogenesis, with broad light intensity gradients in which gametogenesis was successfully induced (Lüning , Lee and Brinkhuis ).…”
mentioning
confidence: 99%
“…For example, the growth rate of Laminaria digitata gametophytes was highest at 10-18 • C, while gametogenesis required lower temperatures (i.e., 10-15 • C), and fertilization and recruitment of sporophytes was optimal at only 5 • C (Martins et al, 2017).…”
Section: B2 Propagation Success: Climate Change Impacts On Early Lifementioning
confidence: 99%
“…However, ocean warming can negatively affect kelp's asexual (sporogenesis) and sexual (gametogenesis) reproduction (Viejo et al, 2011;Bartsch et al, 2013;Roleda, 2016;Martins et al, 2017). The impacts of climate change on the reproduction (both sporogenesis and gametogenesis) and embryogenesis among macroalgae with complex life cycles require further studies.…”
Section: B2 Propagation Success: Climate Change Impacts On Early Lifementioning
confidence: 99%
“…Reproduction in kelps is tightly connected to environmental cues. Gametophytes may enter gametogenesis under the specific combination of nutrients, light, and temperature or remain vegetative if conditions are not favorable (Martins et al, 2017;Bartsch, 2018). In the latter case, vegetative gametophytes are considered to be dormant and may act as a "seed bank" allowing for the recovery of the population after a disturbance, e.g., storms or heat-waves (Edwards, 2000;Barradas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%